Improving OSA screening efficiency with subjective questionnaires: integrating STOP-Bang, ESS, and Berlin - Riken Chen; Yuan Zhang; Weilong Ye; Zhaojun Chen; Weifeng Liao; Huizhao Liao; Tingting Sun; Huan Li; Junfen Cheng; Wang Liu; Weimin Yao; Yitian Yang (Frontiers in Medicine)
ObjectiveTo compare the predictive value of the STOP-Bang questionnaire, the Epworth Sleepiness Scale (ESS), and the Berlin questionnaire, while evaluating the combined application of these tools in a three-step screening strategy for obstructive sleep apnea (OSA).MethodsFrom September 1, 2016, to October 31, 2020, at the Sleep Medicine Center of the First Affiliated Hospital of Guangzhou Medical University, 2,208 suspected OSA patients completed the ESS, STOP-Bang, and Berlin questionnaires and underwent polysomnography (PSG). The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and receiver operating characteristic (ROC) curves were calculated for each questionnaire, and the accuracy and predictive value of combining the STOP-Bang, ESS, and Berlin questionnaires for OSA screening were analyzed.ResultsAmong the individual scales, the Berlin questionnaire had the highest area under the curve (AUC), demonstrating the best diagnostic performance and the highest PPV. The ESS had the smallest AUC and the highest specificity, but the lowest sensitivity and NPV. The STOP-Bang had the highest sensitivity and NPV but the lowest specificity and PPV. When the scales were combined, the AUCs of all combinations were less than 0.7, indicating that the diagnostic performance of the combined scales slightly decreased compared to the individual scales. However, among the combined scales, the AUC of the three-scale combination was higher than that of the two-scale combinations. After combining the questionnaires, specificity and PPV increased, but sensitivity and NPV decreased. Among the two-questionnaire combinations, the sensitivity and NPV of the ESS and STOP-Bang combination were higher than those of the ESS and Berlin questionnaire combination, while specificity and PPV were lower. The combination of all three questionnaires resulted in the highest specificity and PPV, but the lowest sensitivity and NPV.ConclusionAs the number of scales increases, sensitivity and NPV decrease, while specificity and PPV increase. Therefore, we recommend a three-step strategy, combining a STOP-Bang score of 3, an ESS score of 9, and the Berlin questionnaire to improve the specificity and PPV in screening for OSA.